Decreased Plasma Tissue Factor Pathway Inhibitor Levels in Patients with Thrombotic Thrombocytopenic Purpura - Wada, Hideo; Kobayashi, Masayuki; Wakita, Yoshihiro; Shimura, Minori; Nakase, Tutomu; Hiyoyama, Katsuyo; Nagaya, Syousaburou; Minami, Nobuyuki; Nakano, Takeshi; Shiku, Hiroshi (Thrombosis and Haemostasis, 1995)
We measured plasma levels of tissue factor (TF) and tissue factor pathway inhibitor (TFPI) in patients with thrombotic thrombocytopenic purpura (TTP) and disseminated intravascular coagulation (DIC) to examine the relationship between TFPI and vascular endothelial cell injury. TF antigen was detected in the plasma of healthy volunteers, and the levels were significantly increased in the patients with DIC, but decreased slightly in those with TTP. Plasma TFPI levels were significantly decreased in patients with TTP compared with those in healthy volunteers. The concentration of plasma thrombomodulin (TM) antigen was significantly higher in those with TTP than in normal volunteers. One month after treatment, TTP patients showed a significant decrease in plasma TM levels, and a significant increase, in plasma TFPI levels, but plasma levels of TF antigen were not significantly increased. As plasma TFPI/TF ratio was significantly increased after treatment, the hypercoagulable state was therefore improved after treatment. There was no significant difference in plasma TF and TFPI levels between those who achieved complete remission (CR) and those who died. However, plasma TM levels were significantly higher in those who died than in those who achieved CR. Plasma TFPI levels might reflect injury of vascular endothelial cells as do plasma TM levels, and decreased plasma TFPI/TF ratio and vascular endothelial cell injuries might play causative roles in TTP.